Optimization of UWB pyramidal horn antenna with load - Xia, Y; Edwards, D (2006)
For a UWB pyramidal horn antenna with a curved ridge and a fin, the effect of the resistors at the end of the fin on reflection coefficient or return loss is investigated. The results from both simulation and experiment show that it is a very important factor on its performance that these termination resistors well match the impedance at the antenna's end. © 2007 IEEE.